2016
DOI: 10.5665/sleep.6316
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnography in Bolivian Children Native to High Altitude Compared to Children Native to Low Altitude

Abstract: HA native Andean children have more respiratory events when scoring relies on SpO2 desaturation due to inherent SpO2 instability. Use of American Academy of Sleep Medicine scoring criteria may yield false-positive results for obstructive sleep-disordered breathing at HA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
0
15
0
3
Order By: Relevance
“…This phenomenon was also reported by Hill et al, who noted that the ODI ≥ 3% increases from 0.6/h at 500 m a. s. l. to 3.3/h at 3,560 m a. s. l. in children aged 7 to 16 years (Hill, Baya et al, 2016). The changes in the ODI at high altitude are due to the fact that SpO 2 dispersion between individuals becomes wider as altitude increases; this dispersion is more evident during sleep (Ucrós et al., 2020; Hill, Carroll et al, 2016). Hill et al reported a developmental time course for overnight oxygen saturation indices in the Bolivian Andes across childhood and it is possible this may show a U‐shaped curve into adulthood (Hill, Carroll et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was also reported by Hill et al, who noted that the ODI ≥ 3% increases from 0.6/h at 500 m a. s. l. to 3.3/h at 3,560 m a. s. l. in children aged 7 to 16 years (Hill, Baya et al, 2016). The changes in the ODI at high altitude are due to the fact that SpO 2 dispersion between individuals becomes wider as altitude increases; this dispersion is more evident during sleep (Ucrós et al., 2020; Hill, Carroll et al, 2016). Hill et al reported a developmental time course for overnight oxygen saturation indices in the Bolivian Andes across childhood and it is possible this may show a U‐shaped curve into adulthood (Hill, Carroll et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Como sucede con los parámetros respiratorios estos valores son diferentes en la altura (8) . A 2.640 m el parámetro de la AAMS es válido solamente después del año de edad (8) ; a 3.650 m en niños entre 7 y 13 años sí es aplicable (10) .…”
Section: Microdespertaresunclassified
“…Teniendo en cuenta el gran desarrollo que ha tenido la medicina del sueño se hizo esta revisión centrándose en las características del sueño en niños en la gran altura. Para el análisis se encontraron cinco publicaciones de PSM en niños sanos entre los 0 y los 16 años de edad (7)(8)(9)(10)(11) , residentes habituales a gran altura (Tabla 1). Para completar el análisis se hizo una búsqueda sobre la saturación de oxígeno (SpO2) durante el sueño entre los 0.5 meses y los 18 años de edad en alturas >2.500 metros, encontrando cinco publicaciones adicionales (Tabla 2).…”
Section: Introductionunclassified
“…High altitude (HA) exposure is becoming more and more common as the increased human activities in high plateaus and mountains. Most human, even those who lived in plateau for generations (Ebert‐Santos, 2017; Hill et al, 2016), are not totally adapted to HA exposure, as indicated by headache, sickness, poor sleep quality (Sakamoto et al., 2017), cognitive impairment (Chen et al., 2017), polycythemia, pulmonary hypertension (Robinson et al., 2017), right ventricular hypertrophy, and fertility reduction (Parraguez et al., 2013; Simonson, 2015; Whayne, 2014). With the huge demand of heath care for people exposed to HA, various studies were carried to explore mechanisms underlying HA‐induced health challenges.…”
Section: Introductionmentioning
confidence: 99%